PERNIKAHAN TANPA RESTU ORANG TUA: KAJIAN FIKIH MUNAKAHAT DAN 'URF TERHADAP TRADISI PERNIKAHAN NAIK - Jufri, Muhammad; Mustofa, Mutofa (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2025)
This study investigates the practice of “pernikahan naik” (elopement marriage) in Persada Tongra Village, Terangun District, Gayo Lues Regency, Aceh Province, from the perspectives of Islamic law and customary law. “Pernikahan naik” refers to a traditional form of marriage where a man takes the woman he loves to the home of a religious figure (tengku imem) to be married, often without the consent or knowledge of the woman’s parents. This practice is commonly driven by factors such as lack of parental approval, expensive dowries, family disputes, or premarital pregnancy. Although it appears to violate social and legal norms, in the Gayo community, it has become institutionalized through customary procedures and religious involvement. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation involving pesantren alumni couples, customary leaders, and religious figures. Data analysis involved reduction, presentation, and conclusion drawing. The findings reveal that pernikahan naik follows several stages: mutual agreement between the couple, elopement to the religious leader’s residence, and the solemnization of the marriage witnessed by community figures. From the standpoint of Islamic law, such marriages are considered valid as long as they fulfill the essential elements (rukun) and conditions (syarat) of nikah. However, from the customary law perspective, this practice is seen as a violation and may incur sanctions, such as a fine of a goat. In the context of Islamic jurisprudence, although pernikahan naik may be normatively accepted, it can be classified as urf fasid (corrupt custom) because it neglects the obligation to honor the bride’s guardian (wali). Therefore, the study recommends the need for comprehensive legal socialization that integrates Islamic law, statutory regulations, and customary values, to mitigate such practices while preserving local wisdom. This research contributes to a broader understanding of how social dynamics, religious values, and customary systems shape the formation of harmonious families within pesantren and indigenous communities.